There might be a frog in McElligot's Pool: a study of the habitat characteristics and social factors associated with amphibian presence in urban residential gardens in a suburb in Cape Town - Brom, Peta (Department of Environmental and Geographical Science, 2018)
This thesis engages with urban ecology through the lens of garden amphibians within a community in Cape Town. The study explores habitat and maintenance features associated with amphibian presence and the social processes underpinning attitudes towards amphibians, with the aim of strengthening knowledge underpinning the "what" (knowledge of natural requirements), "Why" (social drivers for urban landscape form and management), and the "how" (working with people, for garden biodiversity initiatives. To explore the "Why" component, a social survey was conducted with 192 members of the community. One‐way anova and correspondence analysis were used to explore the relationship between values, culture, knowledge and memories of early childhood experiences against a general attitude towards frogs and toads. The findings are consistent with the theoretical framework of Connectedness To Nature where positive attitudes are supported by normative values, cultural beliefs, knowledge and positive experiences with care‐givers and role‐models. The garden habitat component of the study sought to explore the technical questions of the "What" requirement for amphibian presence in gardens. It was loosely based on the BIMBY tool with adaptations for context and targeted species. 50 gardens were visited and surveyed. They were divided into two groups for comparison: Those in which residents reported amphibian presence, and those which did not. Results indicate that the cape river frog (A. fuscigula) and clicking stream frog (S. grayii), are attracted to gardens with moderate to dense vegetation at groundcover level. Gardens with moderately planted beds were more likely to report frogs if they had additional resources, in particular, ponds and mulch. The "How" question brought together the two themes in a discussion on citizen mobilization and ways in which community groups are successfully implementing urban ecology conservation and reconciliation strategies. This work is important for urban nature conservation which seeks to engage private land‐owners (garden enthusiasts) and community and citizen groups in implementing urban biodiversity projects.